PENGARUH BERBAGAI MEDIA TUMBUH DAN PENAMBAHAN GULA (SUKROSA) TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Fritz Tanza Sitompul; Elza Zuhry; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The cultivation of white oyster mushroom (Pleurotus ostreatus) is not many expanded yet in Indonesia, either the exertion chance or consumtion fulfillment of society. The purpose of the research is to find out the effect of giving various growth media and sugar and get the best combination will increase the production. This research has been conducted in the village of Pandau Jaya of Siak Hulu Kampar district in Riau Province in August until November of 2016. This research was carried out experimentally using a complete randomized design (CRD) factorial consisting of two factor. The first factor is growth media consist of 3 types sawdust, bagasse and tea waste. The second factor is dose of sucrose consist of 4 levels is without sucrose, 40 g, 80 g and 120 g, two factors combined to obtain 12 combined treatments and 4 replication, so there were obtained 48 units experimental each unit countain  2 baglog. Data were analyzed statistically and further test DNMRT at 5 %. The observer parameters is optimal growth of mycelium, pinhead appearance,harvest interval,number of mushrooms,diameter of mushroom hood, weight of mushrooms, biological efficiency. The result showed that the various growing media and the addition of sucrose have an effect on the growth of white oyster mushroom. The combination of growing media of bagasse with the addition of sucrose 40 g yields a mushroom weight of 123.22 g/baglog.Keyword: oyster mushroom, growth media, sugar (sucrose), growth